ANALISIS STABILITAS TIMBUNAN (MAINDAM) BERDASARKAN DATA INSTRUMEN GEOTEKNIK PADA BENDUNGAN SINDANG HEULA SERANG BANTEN - Nanang Sutisna; M. Ichwanul Yusup; Euis Amilia Euis Amilia (LPPM, 2021)
The development of science and technology has obtained supporting technology for monitoring the soil shear force and pore water pressure in the dam, the presence of shear forces against the landfill and pore water pressure through small cavities in the embankment soil in the dam body which can be detected by equipment such as inclinometer and piezometer that have been installed at predetermined points. The application of inclinometer and piezometer technology is used as a support tool for monitoring the movement of landfill and pore water pressure against dams. The embankment dam is the most complex of civilian structures and is very dangerous if damaged. When there is damage to a dam, it will cause a big disaster for the areas that are downstream of the dam. Damage or collapse of a dam can occur due to several things, including overtopping, sliding of the dam slopes (internal erosion or